Purification, characterization, and bioassay of putative protease inhibitors from Hevea brasiliensis latex - Riza Arief PUTRANTO; . SISWANTO; Agustin Sri MULYATNI; Asmini BUDIANI; Radite TISTAMA (E-Journal Menara Perkebunan, 2016)
Lateks yang menyerupai cairan susu putih diperoleh dari penyadapan kulit batang tanaman karet (Hevea brasiliensis). Lateks merupakan sitoplasma dari jaringan pembuluh bernama latisifer yang didalamnya terkandung berbagai macam komponen, termasuk protein-protein penting. Berbagai jenis enzim yang memiliki fungsi terkait pertahanan tanaman dari serangan patogen dan pelukaan telah berhasil dideteksi di dalam lateks, di antaranya protease inhibitor (PI). Protease inhibitor memiliki aktivitas senyawa antifungi sehingga berpotensi untuk  dimanfaatkan sebagai biofungisida. Pada penelitian ini, protease  inhibitor putatif yang berasal dari serum B (lutoid) lateks tanaman karet telah berhasil diisolasi menggunakan teknik Ion Exchange Chroma-tography. Dari total 70 fraksi protein yang diekstrak dari kolom, hanya 26 fraksi yang menunjukkan kadar protein yang terukur. Kandungan protease inhibitor putatif yang di-peroleh berkisar antara 0,0067 hingga 0,022 mL/g serum B dari hasil 3 fraksi terpilih. Aktivitas penghambatan terhadap empat enzim protease (subtilisin A, tripsin, α-kimotripsin, dan papain) menunjukkan karakteristik protease inhibitor putatif tersebut sebagai serine dan/atau cysteine inhibitor protease dengan persentase hambatan di atas 15% terhadap protease target. Hasil SDS-PAGE memperlihatkan pemisahan protein dominan yang diperkirakan merupakan protease inhibitor putatif dengan berat molekul sebesar 21,5 kDa. Uji bioassay aktivitas antifungi secara in vitro dari protease inhibitor memperlihatkan penghambatan pertumbuhan miselium dari fungi Ganoderma boninense, Sclerotium sp., dan Rigidosporus lignosus. [Kata kunci : protease inhibitor, Hevea brasiliensis, lateks, serum B, ion exchange chromatography]AbstractLatex, a milky white liquid, is the main product from rubber tree (Hevea brasiliensis). Latex is the cytoplasm of complex cellular networks named laticifers in which it contains many different components, including important proteins. Various types of enzymes carrying functions associated with plant defense against pathogen and wounding have been detected in latex in which one of these enzymes is protease inhibitor (PI). Plant protease inhibitor has tremendous potential as an antifungal agent which can be developed as biofungicide. In this work, protease inhibitors from B-serum (lutoid) of rubber tree latex were isolated and purified using Ion Exchange Chromatography (IEC) technique. Of the total 70 fractions of proteins extracted from the columns, only 26 fractions showed measurable levels of protein. The concentration of obtained putative protease inhibitors (three fractions of IEC) ranged from 0.007 to 0.022 mL/g B-serum. Inhibitory activity against four protease enzymes (subtilisin A, trypsin, α-chymotrypsin, and papain) showed the characteristics of Hevea putative protease inhibitors from B-serum as serine and/or cysteine protease inhibitors with more than 15% inhibitory activity of target protease. Based on SDS-PAGE visualization, the molecular weight of dominant protein considered as Hevea putative protease inhibitors was 21.5 kDa. In vitro bioassay test of antifungal activity for Hevea putative protease inhibitors showed reduced mycelium growth of Ganoderma boninense, Sclerotium sp., and Rigidosporus lignosus.[Keywords: protease inhibitor, Hevea brasiliensis, latex, B-serum, ion exchange chromatography]